Fish diversity in the tropical nearshore-coastal waters of Bintulu, Sarawak - A., Aishyatul Fatrah; A. D., Nurdiyana; I., Johan (Malaysian Society of Animal Production, 2022)
A study was conducted to observe the diversity and composition of fish at two locations, Bintulu Waterfront (WF) and ABF Beach (ABF) in Bintulu, Sarawak. A standard three-layer mesh gill net of 2.5 cm, 5.0 cm and 7.5 cm mesh size with a length of 15 m were used to collect the fishes. A total of 18 families and 24 species of fish were recorded during the study period. The most dominant family was Carangidae (23.4%) and the most dominant species of fish was Leiognathus equula (26.5%). The number of species recorded at WF (15 species) were higher than at ABF (13 species). Nine fish species were recorded only at ABF where the dominant species is Leiognathus equula. There were 11 fish species present at WF where Megalaspis cordyla was the dominant species. The diversity index at WF (2.192) was higher compared to ABF (1.691). The evenness index was higher at WF (0.809) and ABF (0.659). Twenty-two species of fish recorded were of commercial importance. It was observed that more than 80% of fish individuals were at the juvenile stage indicating the role of coastal lines, to a certain extent as a nursery area. The findings of this study would help prior to conserve and manage the fishery resources of Bintulu coastal water in future.